Evaluation of amine-based solid adsorbents for direct air capture: a critical review. Issue 1 (30th November 2022) - Panda, Debashis; Kulkarni, Vaishnavi; Singh, Sanjay Kumar
Abstract : Direct air capture (DAC) is an emerging technology with the potential to achieve net zero carbon goals. This review highlights various aspects and recent developments in the area of direct air CO2 capture over amine-modified porous solid adsorbents. Abstract : Direct air capture (DAC) emerges as a new technology that can contribute to "negative carbon emission". Recent progress in surface chemistry and material synthesis has allowed a new generation of CO2 adsorbents that can drive the future of DAC and its wide-ranging deployment. This review is intended to shed light on the recent developments in porous amine-based solid sorbents for direct air CO2 capture, adsorbent preparation and characterization, CO2 capture under dry and humid conditions, CO2 adsorption kinetics, adsorption thermodynamics, sorbent regeneration, cyclic stability, essential regeneration techniques, and techno-economic analysis for CO2 capture from air.